PELATIHAN DESAIN PRODUK DAN IKLAN DIGITAL IKM RENGGINANG DI DESA PRAMBONTERGAYANG KECAMATAN SOKO KABUPATEN TUBAN - Faisal Ashari; Eko Wahyu Abryandoko (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2023)
Packaging design and digital advertising are an important part of product marketing. Unique product design, will be an added value for consumers to consider buying a product and digital markets provide information for consumers that cannot be reached by traditional markets so that producers are able to expand market share, therefore the focus of the PKM that the author will do is provide training to the industry the household industry (IRT) Urnika Snacks Rengginang in Prambontergayang Village, Soko District, Tuban Regency, IRT Urnika Snacks Rengginang is widely known in the environment around the sub-district, but the sales that IRT do are still in the traditional way and the IRT packaging is still wrapped in plastic. The method of implementing PKM was carried out using a participatory approach (participatory action research/PAR). We carry out this service program to provide training on the importance of digital advertising supported by unique packaging designs to increase IRT marketing. Service activities regarding packaging design and digital advertising are expected to be able to help Rengginang IRT Prambontergayang Village in marketing snack products so that they can increase the income of the IKM Rengginang.